From climate policy pioneers to climate policy leaders? The examples of the eastern German cities of Potsdam and Rostock - Wolfgang Haupt; Kristine Kern; Janne Lis Irmisch (Urban Research & Practice, 2022)
We illustrate how the two mid-sized post-socialist eastern German cities Potsdam and Rostock have managed to become climate pioneers, despite being located in regions that have been reluctant with regard to climate action. Drawing on municipal documentation and fieldwork interviews, we show how favorable and interrelated conditions concerning a city's socio-demographic, socio-economic, and particularly political situation were more important for progressive climate action than both cities' embeddedness in their respective regions. We also show how the absence of external ambitions and mayoral support hindered Potsdam and Rostock from making the leap from a pioneer to a leader.
Keywords: 710; Climate governance; local governments; leaders; pioneers; post-socialist cities